IAES Consolidated 2025-2027 Workplan and Budget - CGIAR Independent Evaluation and Advisory Service (2025)
At its 21st meeting, the CGIAR System Council approved the consolidated 2025-2027 workplan and budget of CGIAR's Independent Advisory and Evaluation Service, comprising the ISDC, SPIA, their respective secretariats, and the Evaluation Function (SC/M21/DP5).